Pengelolaan Potensi Wisata Bukit Pilar oleh Karang Taruna di Desa Pangkalan Kecamatan Langkaplancar Kabupaten Pangandaran - Dede Rijki Pauzi; Arie Budiawan; Asep Nurdin Rosihan Anwar (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Bukit Pilar, a tourist attraction located in Pangkalan Village, Karang Taruna, Langkaplancar District, Pangandaran Regency, is the subject of research conducted by Karang Taruna of Pangkalan Village with the aim of identifying how the tourism potential of Bukit Pilar is managed. This research uses a descriptive or narrative approach, applying qualitative methods to understand or describe the studied phenomenon. A comprehensive evaluation of all collected data from various sources, such as interviews, observational studies, documents, and conclusions, is the initial step in the data analysis procedures. The results of this research provide insights into how Karang Taruna in Pangkalan Village, Langkaplancar District, Pangandaran Regency, manages the tourism potential of Bukit Pilar. Several factors have contributed to the failure in management, including: (1) The absence of a formal body with a clear hierarchy of responsibilities and a lack of experienced human resources in the fundamentals of tourism and public service. (2) Limited promotion of tourism through social media content creation (e.g., Instagram, TikTok) and the lack of tourism package offerings. (3) Lack of collaboration among local government, investors, and academics in developing sustainable tourism. The obstacles identified in each of these indicators include: (1) The village government has not issued an official decree (SK) assigning Karang Taruna the authority to manage the Bukit Pilar tourism site. There is also a lack of skilled human resources capable of managing the tourism object. (2) Social media has not been effectively utilized, and tourism packages have not been developed to promote Bukit Pilar. (3) The management of Bukit Pilar has not yet coordinated with the tourism office and potential investors. In response to these challenges, the managers of Bukit Pilar are approaching the village government to initiate coordination with the tourism office. However, the management of the Bukit Pilar tourism object still faces various obstacles, resulting in the dimensions and indicators of tourism management not being optimally achieved.